Differences in bioavailability and cognitive-enhancing activity exerted by different crystal polymorphs of latrepirdine (Dimebon®) - Gorin, Boris I.; Tukhovskaya, Elena A.; Ismailova, Alina M.; Slashcheva, Gulsara A.; Lenina, Oksana A.; Petrov, Konstantin A.; Kazeev, Ilya V.; Murashev, Arkady N. (Frontiers in Pharmacology, 2023)
Introduction: Pharmacokinetic characteristics as well as cognitive-enhancing nootropic activity of latrepirdine (Dimebon®) in relationship with its polymorphic forms have been studied in SD and Wistar rats. Methods: The pharmacokinetics of six polymorphs (A, B, C, D, E, F) of latrepirdine were studied in male SD rats after 7 days of oral administration in corn oil at a dose of 10 mg/kg once a day. Blood and brain samples were taken on the 7th day of administration at 15 min, 30 min, 60 min and 120 min after administration and analyzed for latrepirdine content by LC-MS. The cognitive-enhancing nootropic effect was studied in male and female Wistar rats after 9 days of oral administration in corn oil at a dose of 10 mg/kg, after prior administration of scopolamine, an agent that causes memory impairment similar to that in Alzheimer’s disease. The animals’ cognitive function was studied in the passive avoidance test. Results: When studying the pharmacokinetics, the highest bioavailability both in the blood and in the brain was demonstrated by polymorph E, whose AUC was the highest relative to other polymorphs. In the study of the cognitive-enhancing nootropic effect, polymorph E also showed the highest activity, whose values of the latent period of entering the dark chamber did not differ from control animals, and differed from other polymorphs. Conclusion: Thus, the crystal structure has been shown to play a key role in the bioavailability and efficacy of latrepirdine, and polymorph E has also been shown to be a promising drug for the treatment of neurodegenerative diseases associated with memory impairment, such as Alzheimer’s disease.